MANUFACTURERS AND STRICT LIABILITY FOR DEFECTIVE PRODUCTS Wagener v Pharmacare Ltd; Cuttings v Pharmacare Ltd 2003 4 SA 285 (SCA) - Tanya Woker (Obiter, 2023)
For years academics and consumer activists have been calling for manufacturers to be held strictly liable for defective products, irrespective of whether or not they are contractually linked to consumers. In the United States of America, for example, these calls go back as far as the 1940s. The present position in our law is that, unless the action arises out of a contractual relationship, the general principles of delict apply and negligence or intentional misconduct on the part of the manufacturer must be proven by the injured consumer. The problem for consumers is that it is often very difficult for them to do this. This is particularly true in South Africa where we have a highly sophisticated manufacturing industry serving a largely unsophisticated consumer market. Following Ciba-Geigy (Pty) Ltd v Lushof Farms (Pty) Ltd (2002 2 SA 447 (SCA)), some suggested that the Supreme Court of Appeal had left the door open for the courts to recognise strict liability in delict for unintended harm caused by defective products. Neethling and Potgieter in their article “Die Hoogste Hof van Appel laat die Deur Oop vir Strikte Vervaardigersaanspreeklikheid” (2002 TSAR 582) concluded as follows:“Aangesien die appelhofuitspraak in Ciba klaarblyklik nie afwysend staan teenoor die erkenning van strikte risiko-aanspreeklikheid op die gebied van defekte produkte nie, vertrou ons dat die howe in verdienstelike gevalle hieraan gevolg sal gee” (586).However, in Wagener v Pharmacare Ltd; Cuttings v Pharmacare Ltd (2003 4 SA 285 (SCA)) the Supreme Court of Appeal closed the door, holding instead that introducing strict liability for manufacturers is the prerogative of the legislature and not the courts.